The Essential Oil of Coleus Amboinicus Loureiro Chemical Composition and Evaluation of Insect Anti-Feedant Effects - Valera, Dilexa; Rivas1Roimar; Avila, Jorge Luis; Aubert, Lianne; Alonso-Amelot, Miguel; Usubillaga, Alfredo (Ciencia)
The chemical composition of the essential oil of Coleus amboinicus Loureiro, an aromatic plant with ethnobotanical uses, has been analyzed by gas chromatography coupled with mass spectrometry and its insect antifeedant properties examined using Sitophilus oryzae and Tribolium castaneum, two important stored grain insect pests. Two samples were collected, one at Rancherías (1.100 meters above sea level) and at the Medicinal Plants Garden, Faculty of Pharmacy, Mérida (1400 m.a.s.l.). Carvacrol and p-cymene were found to compose most of the volatile material, 74.5% (Mérida) and 74.1% (Rancherías). The oil from Mérida, was found to contain a larger proportion of carvacrol (64.7%) and sesquiterpenes (17.4%) than the oil from Rancherias (55.3% and 10.5%). On the other hand the oil from Rancherías was richer in p-cymene (18.8% against 9.8%) and monoterpenes. The essential oil in large dosage (1.25%) on hardened flour feeding disks was found unable to induce any negative response in the feeding behavior of the test insects, nor was any mortality recorded within the 60 h of exposure of the bioassays